The Implementation of Reading Aloud Strategy to Develop Student Skill Responding to Expression of Giving Good and Bad News - Putri, Maudy Yuniarti; Gaffar, Muhammad Andriana (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
Speaking skills are a very important aspect of learning English to establish good communication. However, many students still need help expressing what they want to convey, be it ideas, ideas in a reading, or opinions when communicating, because of a lack of confidence from students. Thus, this study aims to improve students’ speaking skills and to find out the factors and causes of students’ difficulties in understanding reading by applying the learning method of reading aloud in learning text reports. This research was conducted at SMKN 1 SOREANG class X-TKJ (Network Computer Engineering) 1 with 36 participants. This research uses qualitative methods with a Classroom Action research approach. Data collection techniques in this study used three techniques, namely, Instruments: observations, field notes, and interviews. Based on the results of the study, the researcher can conclude that the application of the aloud reading learning method carried out by the teacher can run smoothly because, by the procedure, application of reading aloud, students can follow the teacher’s direction well. In this learning process, students are very enthusiastic, and this encourages student learning motivation, especially in reading English texts; besides that, students can improve significantly in student speaking skills In several aspects it has so that students can be responsive when answering questions related to the reading that the teacher gives quickly. Therefore, based on the results of the research, some of the consequences of students’ difficulties in speaking skills can be overcome by applying the method of learning to read aloud by increasing aspects of speaking skills in students, namely: 1) Fluency, 2) Pronunciation; 3) Intonation; 4) Accuracy.